Ultra-Low-Level Laser Stimulation of LU7 Lieque Promotes Breath Functionality: Could it be of help in Covid 19 Rehabilitation? - A Multiple Case Report - Vanzini, Marzio; Gullà, Daniele; Gallamini, Michele (International Journal of Innovative Research in Medical Science, 2021)
The burden of post COVID rehabilitation is and will be a strong concern for healthcare stakeholders. The Traditional Chinese Medicine is suggesting the application of acupuncture as a dependable tool to be inserted in the rehabilitation project. Libralux, an ultra-low-level-laser stimulator has proven its effectiveness as acupuncture stimulator. In this paper we report the respiratory cycle modifications obtained through the stimulation with Libralux of the acupoint LU7 LieQue of three healthy individuals. Modifications were observed instrumentally by means of an innovative high-resolution camera plotting the chest expansion vs. time. The results demonstrate a remarkable increase in respiration depth and in the contemporary reduction of the respiration frequency within 20 minutes from the 20 sec bilateral stimulation of LU7 LieQue acupoint. The worthiness of a specific full double-blind trial is suggested also in view of the marginal contra-indications, the rapid execution and, most of all, the great potential benefit of the inclusion of a laser acupunctural stimulation in the post COVID rehabilitation project.